2020
DOI: 10.3390/cells9112393
|View full text |Cite
|
Sign up to set email alerts
|

Tumour PD-L1 Expression in Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: : Antibodies against programmed death-1 (PD-1), and its ligand, (PD-L1) have been approved recently for the treatment of small-cell lung cancer (SCLC). Although there are previous reports that addressed PD-L1 detection on tumour cells in SCLC, there is no comprehensive meta-analysis on the prevalence of PD-L1 expression in SCLC. We performed a systematic search of the PubMed, Cochrane Library and EMBASE databases to assess reports on the prevalence of PD-L1 expression and the association between PD-L1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 90 publications
2
39
0
Order By: Relevance
“…Furthermore, the positive group for 1/3 PD-L1 assays was observed in 31 (52.5%) of the total of 59 patients with SCLC. A recent meta-analysis of PD-L1 expression in SCLC, which included 27 studies enrolling a total of 2,792 patients, reported that the pooled estimate of PD-L1 expression was 26.0% (19). However, there were large differences in the rate of PD-L1 expression between the studies included, varying from 0% to 82.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the positive group for 1/3 PD-L1 assays was observed in 31 (52.5%) of the total of 59 patients with SCLC. A recent meta-analysis of PD-L1 expression in SCLC, which included 27 studies enrolling a total of 2,792 patients, reported that the pooled estimate of PD-L1 expression was 26.0% (19). However, there were large differences in the rate of PD-L1 expression between the studies included, varying from 0% to 82.8%.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of clinical impact as a predictive and/or prognostic biomarker of PD-L1 expression in SCLC is scarce and conflicting. Recent meta-analyses of clinical impact of PD-L1 expression in SCLC revealed inconsistent results (18,19). Thus, the association of PD-L1 expression in SCLC with clinicopathological factors warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Although positive PD-L1 expression appears to show better OS in SCLC patients, using it as a reliable predictive marker requires further large scaled studies. In a meta-analysis, the pooled HR of all studies was 0.86 (95% CI: 0.49-1.50, P=0.588) indicating that positive PD-L1 expression demonstrated a trend towards longer OS in SCLC patients (14). However, in the Checkmate 032 study, only 17% of patients had ≥1% PD-L1 expression and 5% had ≥5% PD-L1 expression, and the response to nivolumab monotherapy or a combination with ipilimumab occurred irrespective of the PD-L1 expression levels (21).…”
Section: Pd-l1 and Pd-1 Expressionmentioning
confidence: 99%
“…However, despite some observed correlations, there is a lack of concrete support for the use of PD-L1 expression levels in SCLC as a predictive biomarker for immunotherapy response (29). First, the pooled prevalence of PD-L1 expression is lower compared to those reported in non-small cell lung cancer (NSCLC), which are influenced by IHC evaluation cut-off values, PD-L1 staining pattern, the quality of the study's methodological characteristics, specimen acquisition, and other technical problems such as antibody staining and tissue fixation (14,30,31). Second, PD-L1 expression heterogeneity is not fully captured by small piece of tissue.…”
Section: Pd-l1 and Pd-1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation